Reevaluation of the role of parallel fiber synapses in delay eyeblink conditioning in mice using Cbln1 as a tool - Emi, Kyoichi; Kakegawa, Wataru; Miura, Eriko; Ito-Ishida, Aya; Kohda, Kazuhisa; Yuzaki, Michisuke (Frontiers in Neural Circuits, 2013)
The delay eyeblink conditioning (EBC) is a cerebellum-dependent type of associative motor learning. However, the exact roles played by the various cerebellar synapses, as well as the underlying molecular mechanisms, remain to be determined. It is also unclear whether long-term potentiation (LTP) or long-term depression (LTD) at parallel fiber (PF)–Purkinje cell synapses is involved in EBC. In this study, to clarify the role of PF synapses in the delay EBC, we used mice in which a gene encoding Cbln1 was disrupted (cbln1–/– mice), which display severe reduction of PF–Purkinje cell synapses. We showed that delay EBC was impaired in cbln1–/– mice. Although PF-LTD was impaired, PF-LTP was normally induced in cbln1–/– mice. A single recombinant Cbln1 injection to the cerebellar cortex in vivo completely, though transiently, restored the morphology and function of PF–Purkinje cell synapses and delay EBC in cbln1–/– mice. Interestingly, the cbln1–/– mice retained the memory for at least 30 d, after the Cbln1 injection’s effect on PF synapses had abated. Furthermore, delay EBC memory could be extinguished even after the Cbln1 injection’s effect were lost. These results indicate that intact PF–Purkinje cell synapses and PF-LTD, not PF-LTP, are necessary to acquire delay EBC in mice. In contrast, extracerebellar structures or remaining PF–Purkinje cell synapses in cbln1–/– mice may be sufficient for the expression, maintenance, and extinction of its memory trace.